Sex Chromosome Evolution and Genomic Divergence in the Fish Hoplias malabaricus (Characiformes, Erythrinidae) - Sember, Alexandr; Bertollo, Luiz A. C.; Ráb, Petr; Yano, Cassia F.; Hatanaka, Terumi; de Oliveira, Ezequiel A.; Cioffi, Marcelo de Bello (Frontiers in Genetics, 2018)
The Erythrinidae family (Teleostei: Characiformes) is a small Neotropical fish group with a wide distribution throughout South America, where Hoplias malabaricus corresponds to the most widespread and cytogenetically studied taxon. This species possesses significant genetic variation, as well as huge karyotype diversity among populations, as reflected by its seven major karyotype forms (i.e. karyomorphs A-G) identified up to now. Although morphological differences in their bodies are not outstanding, H. malabaricus karyomorphs are easily identified by differences in 2n, morphology and size of chromosomes, as well as by different evolutionary steps of sex chromosomes development. Here, we performed comparative genomic hybridization (CGH) to analyse both the intra- and inter-genomic status in terms of repetitive DNA divergence among all but one (E) H. malabaricus karyomorphs.Our results indicated that they have close relationships, but with evolutionary divergences among their genomes, yielding a range of non-overlapping karyomorph-specific signals. Besides, male-specific regions were uncovered on the sex chromosomes, confirming their differential evolutionary trajectories. In conclusion, the hypothesis that H. malabaricus karyomorphs are result of speciation events was strengthened.